Effect of Plant Extracts on the Characteristics of Silver Nanoparticles for Topical Application - Ioanna K. Siakavella; Fotini Lamari; Dimitrios Papoulis; Malvina Orkoula; Patroula Gkolfi; Michail Lykouras; Konstantinos Avgoustakis; Sophia Hatziantoniou (Pharmaceutics, 2020)
Silver nanoparticles (AgNPs) were synthesized using hydroalcoholic extracts of dittany (Origanum dictamnus), sage (Salvia officinalis), sea buckthorn (Elaeagnus rhamnoides, syn. Hippophae rhamnoides), and calendula (Calendula officinalis) as reducing agents. AgNPs synthesized using NaBH4 and citric acid were used as control. The impact of the origin of the extract and preparation conditions (light, temperature, reaction time) on the properties of the synthesized AgNPs was investigated. The structure, morphology, composition, physicochemical characteristics, and colloidal stability were characterized using dynamic laser scattering (DLS), ultraviolet-visible spectrophotometry (UV–/Vis), XRD, X-ray fluorescence (XRF), TEM, and FTΙR. The reduction of total phenolic and flavonoid content of the extracts after the reaction of AgNPs synthesis was also determined. Low IC50 values for all types of AgNPs revealed good antioxidant activity, attributable to the phenolic and flavonoid content of their surface. The results suggest that plant extract selection is important to the green synthesis of AgNPs because it affects the kinetics of their synthesis as well as their morphology, physicochemical characteristics, and colloidal stability. In vitro permeation studies on porcine skin revealed that AgNPs remained at the upper layers of stratum corneum and did not penetrate the skin barrier after 4 h of cutaneous application suggesting the safety of their application on intact skin for a relatively short time.